2007
DOI: 10.1016/j.jorganchem.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new carbbenzyloxymethylenetriparatolylphosphorane ylide and study of its reaction with mercury(II) halides: Spectral and structural characterization

Abstract: A new carbbenzyloxymethylenetriparatolylphosphorane ylide (BTPY), {(p-tolyl) 3 PCHCOOCH 2 C 6 H 5 },was synthesized and characterized with elemental analysis as well as various spectroscopic techniques. The reactions of the title ylide with mercury(II) chloride, mercury(II) bromide and mercury(II) iodide in equimolar ratios using dry methanol as solvent have yielded [BTPY AE HgCl 2 ] 2 (1), [BTPY AE HgBr 2 ] 2 (2) and [BTPY AE HgI 2 ] 2 (3), respectively. Single crystal X-ray analysis of 2 reveals the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…The m (P + -C À ) band, which is also diagnostic of the coordination modes, occurs at lower frequencies for complexes in comparison to the parent ylides, consistent with some removal of electron density in the P-C bonds [10][11][12]. C-coordination causes an increase in m (CO) and decrease in m (P + -C À ) while, for O-coordination a lowering for both frequencies is expected [21].…”
Section: Spectroscopymentioning
confidence: 55%
See 2 more Smart Citations
“…The m (P + -C À ) band, which is also diagnostic of the coordination modes, occurs at lower frequencies for complexes in comparison to the parent ylides, consistent with some removal of electron density in the P-C bonds [10][11][12]. C-coordination causes an increase in m (CO) and decrease in m (P + -C À ) while, for O-coordination a lowering for both frequencies is expected [21].…”
Section: Spectroscopymentioning
confidence: 55%
“…It must be noted that O-coordination of the ylide generally leads to the formation of a mixture of cisoid and transoid isomers, giving rise to two different signals in 31 P and 1 H NMR spectra (Chart 1) [18]. The 31 P nuclei shielding of the complexes appeared to be lower by about 4.5-8 ppm with respect to the parent ylides also indicating that coordination of the ylide has occurred [8,[10][11][12]36]. Satellites due to coupling to 199 Hg for ylidic complexes of Hg(II) are only observed at low temperature [10,36] or by solid-state 31 P NMR [36] and also in the case of Hg(NO 3 ) 2 Á H 2 O as metal source [12].…”
Section: Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…It must be noted that O-coordination of the ylide generally leads to the formation of cisoid and transoid isomers giving rise to two different signals in 31 P and 1 H NMR (Scheme 1) [7]. The 31 P NMR spectra at room temperature clearly exhibit the previously mentioned satellites (8% intensity each, 2 J PHg $295 Hz) while these satellites for ylidic complexes of Hg(II) halides are only observed at low temperature [5,19,20,22] or by solid state 31 P NMR [22]. Variable temperature 31 P NMR study on 2d, using DMSO-d 6 as solvent showed that disappearance of satellites occurs when the a: X = Cl, Ar = C 6 H 5 b: X = Cl, Ar = C 6 H 4 -CH 3 c: X = NO 2 , Ar = C 6 temperature is increased to 65°C (Fig.…”
Section: Spectroscopymentioning
confidence: 80%
“…C-coordination causes an increase in m(CO) and decrease in m(P + -C À ) while, for O-coordination, a lowering for both frequencies is expected. The m(P + -C À ) which is also diagnostic for the coordination occurs at lower frequencies for the complexes, suggesting some removal of electron density in the P-C bond [19,20].…”
Section: Spectroscopymentioning
confidence: 93%